Perilaku Sosial Antar Umat BeragamaTerhadap Anak- Anak di Kabupaten Ngawi - Tanti, Amalia Vidra; Fauzi, Agus Machfud (Edugama: Jurnal Kependidikan dan Sosial Keagamaan, 2023)
Indonesia is a pluralistic nation with a wide range of diversity, including social, political, racial, cultural, and religious ones. Religious differences frequently result in strained relationships between members of a community, especially kids in Ngawi Regency. Religion in the Ngawi Regency community naturally provides a blend of individual and group characters in socializing and will influence social behavior patterns against the backdrop of cultural diversity. The goal of the study was to use interviewing and observational data gathering methods to understand how interreligious social conduct toward children in Ngawi Regency. The findings of this study reveal that youngsters in Ngawi Regency exhibit interreligious social conduct extremely well, happily, amicably, enthusiastically, and preserving numerous community activities.